2007
DOI: 10.1016/j.ydbio.2007.09.052
|View full text |Cite
|
Sign up to set email alerts
|

Co-factors of LIM domains (Clims/Ldb/Nli) regulate corneal homeostasis and maintenance of hair follicle stem cells

Abstract: The homeostasis of both cornea and hair follicles depends on a constant supply of progeny cells produced by populations of keratin (K) 14-expressing stem cells localized in specific niches. To investigate the potential role of Co-factors of LIM domains (Clims) in epithelial tissues, we generated transgenic mice expressing a dominant-negative Clim molecule (DN-Clim) under the control of the K14 promoter. As expected, the K14 promoter directed high level expression of the transgene to the basal cells of cornea a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 62 publications
3
31
0
Order By: Relevance
“…Known to be important for stemness, CLIM2 is required for the maintenance of fetal and adult hematopoietic stem cells (5). It is also required for maintenance of epithelial stem cells in the crypts of the small intestine (6), in the bulge of hair follicles (7), and in the basal layer of the mammary gland (8). Intriguingly, CLIM2 has also been shown to regulate the final stages of erythroid differentiation (9).…”
Section: Climsmentioning
confidence: 99%
See 2 more Smart Citations
“…Known to be important for stemness, CLIM2 is required for the maintenance of fetal and adult hematopoietic stem cells (5). It is also required for maintenance of epithelial stem cells in the crypts of the small intestine (6), in the bulge of hair follicles (7), and in the basal layer of the mammary gland (8). Intriguingly, CLIM2 has also been shown to regulate the final stages of erythroid differentiation (9).…”
Section: Climsmentioning
confidence: 99%
“…To avoid the embryonic lethality and the complex issue of redundancy, we developed a mouse expressing a dominant negative (DN) CLIM under the Krt14 promoter (K14-DN-Clim), targeting DN-CLIM to the basal layer of stratified epithelial tissues, including epidermis, hair follicles, mammary gland, and cornea (7,15). The K14-DNClim mice exhibit decreased numbers of hair follicle stem cells, resulting in hair loss, and have abnormal corneas (7).…”
Section: Climsmentioning
confidence: 99%
See 1 more Smart Citation
“…In mice the LDB1-LHX2 complex functions in the maintenance of stem cells in hair follicles 10,47 and possibly in limb development. 48 a similar function was suggested for LDB1 in intestinal crypts 49 and for LDB1, 50 and LHX2, 51 in hematopoiesis.…”
Section: Modularity Of Chip/ldb Transcription Complexes Regulates Celmentioning
confidence: 99%
“…To assess which Eph receptors and ephrins that are expressed in the skin, we first analyzed publically available microarray data derived from either telogen [29] or early and late anagen hair follicles [30] from adult mouse whole back skin. We found that several members of both A and B class receptors and ligands were expressed in telogen follicles (Fig.…”
Section: Multiple Ephrins and Eph Receptors Are Expressed In The Skinmentioning
confidence: 99%